The marketing revolution: a radical manifestation for dominating the marketplace - Clancy, Kevin (New York: Harper Bussiness, 1991)
Is one of the most marketing books of the decade, are offereing a second chance who have not kept up with the changing market place,it is a create in concise guide to how to be succesfull in the 90's in adv beyond.
Incluye bibliografía
Keywords: Marketing; Publicidad